Effects of the Affordable Care Act on Consumer Health Care Spending and Risk of Catastrophic Health Costs - Sarah A. Nowak, Christine Eibner (RAND Corporation, 2013)
This study examines the likely effects of the Affordable Care Act (ACA) on average annual consumer health care spending, the risk of catastrophic medical costs, and average annual consumer health spending and the risk of catastrophic medical costs for low-income individuals in two large states: one in which Medicaid will not be expanded (Texas) and one in which expansion appears unlikely but remains undecided as of August 2013 (Florida). The ACA will have varied impacts on individuals’ and families’ spending on health care, depending on income level and on estimated 2016 insurance status without the ACA. The authors find that average out-of-pocket spending is expected to decrease for all groups considered in the analysis, although decreases in out-of-pocket spending will be largest for those who would otherwise be uninsured. People who would otherwise be uninsured who transition to the individual market under the ACA will have higher total health care spending on average after implementation of the ACA because they will now incur the cost of health insurance premiums. The authors also find that risk of catastrophic health care spending will decrease for individuals of all income levels for the insurance transitions considered; decreases will be greatest for those at the lowest income levels. Case studies found that in Texas and Florida, Medicaid expansion would substantially reduce out-of-pocket and total health care spending for those with incomes below 100 percent of the federal poverty level, compared with a scenario in which the ACA is implemented without Medicaid expansion. Expansion would reduce the risk of high medical spending for those covered under Medicaid who would remain uninsured without expansion